Unexpected uterine leiomyosarcoma in a woman with multiple myomas treated with ulipristal acetate: case report and literature review. (4th March 2018) - Modaffari, Paola; D'alonzo, Marta; Garbagnati, Marta; Pecchio, Silvia; Menato, Guido; Biglia, Nicoletta
Abstract: Ulipristal acetate (UPA) has been recognized as an alternative strategy to surgery in the management of symptomatic women with uterine fibroids. We present a case report on a woman with hereditary fibrinogen deficiency exclusively treated with UPA for myoma-related menorrhagia and abdominal pain, who subsequently underwent a hysterectomy because of clinical worsening. A FIGO IB uterine leiomyosarcoma was found among multiple myomas. A review of the literature found two other cases of uterine leiomyosarcoma in patients treated with UPA: clinical data are reported. The aim of this case report is to increase clinicians' awareness that, although rare, leiomyosarcoma can develop in a uterus with multiple myomas and no reliable diagnostic tools exist yet. Thus, a clinical and instrumental careful reevaluation and patient counseling should be a priority when planning to repeat UPA treatment cycles.